Treatment-related Decisional Conflict, Quality of Life, and Comorbidity in Older Adults with Cancer - Jeannette M Kates (Elsevier, 2018)
Objective: The present study aims to examine the relationships between and among cancer treatment-related decisional conflict, quality of life, and comorbidity in older adults with cancer. Methods: A convenience sample of 200 older adults was recruited from outpatient medical oncology and radiation oncology practices in the northeastern United States. A cross-sectional, descriptive, correlational study design was used employing a survey method. Survey instruments included the Decisional Conflict scale (DCS) (with five subscales, including informed, values clarity, support, uncertainty, and effective decision); Self-administered comorbidity questionnaire (SCQ); European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (including five function scales, three symptom scales, a global health/quality of life scale, and six single items); and an investigator-developed demographic form. Results: The mean total DCS score was 22.1 (±12.5). The uncertainty subscale had the highest mean of the subscales (29.2 ± 18.2). The mean score for global health status/quality of life was 44.2 (±20.7). The mean score of the SCQ was low (9.6 ± 4.1). Significant positive relationships were identified between decisional conflict and quality of life (P = 0.009) and quality of life and comorbidity (P = 0.001). Multiple linear regression analysis found statistically significant relationships for total decisional conflict score and the five decisional conflict scale subscales. Conclusions: Results may suggest a relationship between decisional conflict and quality of life, as well as the quality of life and comorbidity. In addition, there are several physical, emotional, and spiritual factors that may positively or negatively impact decisional conflict.